Transcriptional and metabolic analysis of oleic acid synthesis in seedless and tenera oil palm species - Xu, Wen; John Martin, Jerome Jeyakumar; Li, Xinyu; Liu, Xiaoyu; Cheng, Shunghong; Cao, Hongxing (Frontiers in Plant Science, 2025)
The oil palm (Elaeis guineensis Jacq.) is a perennial oilseed crop whose mesocarp produces palm oil rich in the unsaturated fatty acid oleic acid, known for its oxidative stability and cardiovascular health benefits. However, the regulatory mechanisms and pathways responsible for variations in oleic acid biosynthesis during fruit development remain inadequately elucidated. The study examined the mesocarp of oil palm fruits from three developmental stages in seedless and Tenera varieties to evaluate oleic acid content. Fruits from Seedless (MS) and Tenera (MT) oil palms, pollinated for 95 days (MS1 and MT1), 125 days (MS2 and MT2), and 185 days (MS3 and MT3), were analyzed using metabolomics via liquid chromatography-tandem mass spectrometry (LC-MS/MS). RNA sequencing was conducted to profile gene expression associated to oleic acid biosynthesis and accumulation. Differential genes and metabolites were mapped and functionally enriched through KEGG pathway analysis. The result revealed that SAD, FabD, LACS6, BC, FabB, and FabI were positively associated with oleic acid content, whereas LACS9 exhibited either a negative or strongly negative correlation. By integrating metabolomic and transcriptomic techniques, this study elucidates the distinct mechanisms of oleic acid biosynthesis in seedless and thin-shelled oil palm varieties. These findings provide a scientific foundation for enhancing oleic acid content and improving the quality of oil palm-derived products.